2016
DOI: 10.1007/s12262-016-1564-0
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in the HIV Era: a South African perspective

Abstract: The relationship between HIV infection and the clinical spectrum of appendicitis has not been fully elucidated in the South African context. The aim of this study is to compare the surgical management, histopathology, and outcomes between HIV-positive and HIV-negative patients undergoing surgery for appendicitis. A retrospective chart analysis was performed of 50 patients who underwent surgery for appendicitis at King Edward VIII Hospital, Durban, South Africa between January 2012 and December 2012. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
(21 reference statements)
1
14
1
Order By: Relevance
“…An HIV seroprevalence of 13.4% in this cohort of patients is not negligible and is comparable to data from other Sub-Saharan centres. Gigabhoy et al (4) recently showed that the HIV prevalence in patients undergoing appendectomy at a large tertiary urban hospital is 28%. In a Tanzanian study conducted at a major referral centre, the prevalence was found to be 13.1% (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An HIV seroprevalence of 13.4% in this cohort of patients is not negligible and is comparable to data from other Sub-Saharan centres. Gigabhoy et al (4) recently showed that the HIV prevalence in patients undergoing appendectomy at a large tertiary urban hospital is 28%. In a Tanzanian study conducted at a major referral centre, the prevalence was found to be 13.1% (6).…”
Section: Discussionmentioning
confidence: 99%
“…The laparotomy rate was higher in HIV+ patients (72.2% vs. 41.3%, P=0.03). Previous authors have ascribed this operative approach to the high rate of perforation and peritonitis, that occurdue to the delay in presentation of these patients (4,6). The morbidity relates predominantly to Surgical Site Infections, and is reduced with a laparoscopic approach (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such observation can be also endorsed by the fact that the appendix is also part of the gut lymphoid tissues and this may further explain the involvement of the mucosal B and T cells and the replication of the HIV virus in the appendix. 10,11 The role of immune status and CD4 count is also linked with AA. For example, Bedada et al 11 showed that high postoperative complications and mortality in HIV patients with AA can be associated with a CD4 count <200.…”
Section: Hiv and Appendicitismentioning
confidence: 99%